Giải pt `1) ( 3x – 2 ) ( 4x -7 )3x ² = 0` `2) ( 3,1x – 6,2) ( 0,5x + 1 ) = 0` `3) ( 3x – 2 ) (5x + 5 ) = 0` `4) ( x – 1 ) ( x

Giải pt
`1) ( 3x – 2 ) ( 4x -7 )3x ² = 0`
`2) ( 3,1x – 6,2) ( 0,5x + 1 ) = 0`
`3) ( 3x – 2 ) (5x + 5 ) = 0`
`4) ( x – 1 ) ( x + 2 ) ( x -3 ) = 0`
`5) (5x + 3 ) ( x ² + 4 ) ( x – 4 ) = 0`

2 bình luận về “Giải pt `1) ( 3x – 2 ) ( 4x -7 )3x ² = 0` `2) ( 3,1x – 6,2) ( 0,5x + 1 ) = 0` `3) ( 3x – 2 ) (5x + 5 ) = 0` `4) ( x – 1 ) ( x”

  1. \bb 1)
    (3x-2).(4x-7).3x^2=0
    <=>\(\left[ \begin{array}{l}3x-2=0\\4x-7=0\\3x^2=0\end{array} \right.\) 
    <=>\(\left[ \begin{array}{l}3x=2\\4x=7\\x^2=0\end{array} \right.\) 
    <=>\(\left[ \begin{array}{l}x=\dfrac{2}{3}\\x=\dfrac{7}{4}\\x=0\end{array} \right.\) 
    Vậy S={2/3; 7/4; 0}
    $\\$
    \bb 2)
    (3,1x-6,2).(0,5x+1)=0
    <=>3,1(x-2).(0,5x+1)=0
    <=>\(\left[ \begin{array}{l}x-2=0\\0,5x+1=0\end{array} \right.\) 
    <=>\(\left[ \begin{array}{l}x=2\\x=-2\end{array} \right.\) 
    Vậy S={2; -2}
    $\\$
    \bb 3)
    (3x-2).(5x+5)=0
    <=>(3x-2).5.(x+1)=0
    <=>\(\left[ \begin{array}{l}3x-2=0\\x+1=0\end{array} \right.\) 
    <=>\(\left[ \begin{array}{l}x=\dfrac{2}{3}\\x=-1\end{array} \right.\) 
    Vậy S={2/3; -1}
    $\\$
    \bb 4)
    (x-1).(x+2).(x-3)=0
    <=>\(\left[ \begin{array}{l}x-1=0\\x+2=0\\x-3=0\end{array} \right.\) 
    <=>\(\left[ \begin{array}{l}x=1\\x=-2\\x=3\end{array} \right.\) 
    Vậy S={1; -2; 3}
    $\\$
    \bb 5)
    (5x+3).(x^2+4).(x-4)=0
    <=>\(\left[ \begin{array}{l}5x+3=0\\x^2+4=0\\x-4=0\end{array} \right.\) 
    <=>\(\left[ \begin{array}{l}5x=-3\\x^2=-4(vô lý)\\x=4\end{array} \right.\) 
    <=>\(\left[ \begin{array}{l}x=-\dfrac{3}{5}\\x=4\end{array} \right.\) 
    Vậy S={-3/5; 4}
     

    Trả lời

Viết một bình luận

Câu hỏi mới